2010
DOI: 10.1111/j.1365-2575.2007.00253.x
|View full text |Cite
|
Sign up to set email alerts
|

The pragmatic quality of Resources- Events-Agents diagrams: an experimental evaluation

Abstract: The Resources-Events-Agents (REA) model is a semantic data model for the development of enterprise information systems. Although this model has been proposed as a benchmark for enterprise information modelling, only few studies have attempted to empirically validate the claimed benefits of REA modelling. Moreover, these studies focused on the evaluation of REA-based system implementations rather than directly assessing the REA-modelled conceptual schemas that these systems are based on. This paper presents a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 38 publications
0
21
0
2
Order By: Relevance
“…Despite these research efforts, most conceptual modeling texts do not emphasize domain-specific patterns nor analogical reuse, and conceptual modeling notations are considered as general tools that must be mastered independently of the application domain. Poels et al (2007) and Poels (2009) showed that UML class diagrams that are used as conceptual representations of enterprise transaction cycles (e.g., order-to-cash, procure-topay, produce-to-stock, etc. ) are better understood by business users, both objectively (in terms of performance in model comprehension tasks) and subjectively (in terms of perceived ease of understanding), if these diagrams are consistently constructed using resource-event-agent patterns.…”
Section: Applied Domain Knowledge Quality (D3)mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these research efforts, most conceptual modeling texts do not emphasize domain-specific patterns nor analogical reuse, and conceptual modeling notations are considered as general tools that must be mastered independently of the application domain. Poels et al (2007) and Poels (2009) showed that UML class diagrams that are used as conceptual representations of enterprise transaction cycles (e.g., order-to-cash, procure-topay, produce-to-stock, etc. ) are better understood by business users, both objectively (in terms of performance in model comprehension tasks) and subjectively (in terms of perceived ease of understanding), if these diagrams are consistently constructed using resource-event-agent patterns.…”
Section: Applied Domain Knowledge Quality (D3)mentioning
confidence: 99%
“…16 Transaction cycle representation (as a UML class diagram) constructed using a domain-specific pattern (resource-event-agent conceptual modeling structures) (based on (Poels 2009 applied domain knowledge quality (D3)). Furthermore, as demonstrated in (Poels, et al, 2007), business users like accountants and auditors get a far better understanding of the transaction cycle modeled if a diagram like Fig. 16 is used (i.e., higher pragmatic quality (P7)).…”
Section: Applied Domain Knowledge Quality (D3)mentioning
confidence: 99%
“…Then, more than a century ago, manual EZS replaced manual NES definitively because of the inherent control deficiencies of NES (Ashworth, 1886;Barra and Griggs, 2007;Bardsley, 1900;Craig, 1898;Marshall, 1895). A computerised environment has not solved these inherent control deficiencies and the financial accounting and auditing profession has consequently largely ignored computerised NES (McCarthy, 2003;Poels et al, 2007). Just as EZS solved certain internal control deficiencies of NES in manual systems, it continues to solve those NES deficiencies in a computerised environment.…”
Section: Background For the Researchmentioning
confidence: 99%
“…Nonetheless, modern NES such as REA have proven useful as modelling tools for building databases for business (e.g., Bradford et al, 2007;Callaghan et al, 2002;Dunn et al, 2005;Gerard, 2005;Jones et al, 2002Jones et al, , 2005Jones et al, -2006Poels et al, 2007), including non-accounting databases (e.g., Vymetal et al, 2008). Consequently, there is room for both NES and EZS in a modern AIS: one as a database design tool, the other as the target of that design.…”
Section: Background For the Researchmentioning
confidence: 99%
“…In our research we focus on the act of model creation, thereby complementing the active stream of research investigating process model interpretation [e.g., 51,56].…”
Section: Data Collection Strategymentioning
confidence: 99%